The Role of PCNU in Strengthening Aswaja An-Nahdliyah Values and Religious Moderation in Metro City - Tanyizul Maksum; Jaenullah Jaenullah; Sunarto Sunarto (Assyfa Journal of Islamic Studies, 2025)
This study examines the role of the Nahdlatul Ulama Branch Leadership (PCNU) in Metro City in strengthening Aswaja An-Nahdliyah values and religious moderation. Religious moderation has become increasingly urgent in Indonesia's pluralistic society amid rising radicalism and transnational ideologies that threaten national integration. As the largest Islamic organization in Indonesia, Nahdlatul Ulama (NU) bears responsibility for instilling moderate Islamic values to counter extremism. This qualitative field research employed observation, documentation, and in-depth interviews with key informants including PCNU administrators. Data analysis was conducted descriptively-analytically. The findings reveal that PCNU Metro City strengthens Aswaja values through three primary channels: structural (formal cadre training: PKD, PDPKNU, PMKNU), cultural (pesantren and majelis taklim), and intellectual (Bahtsul Masail Institute). Actualization manifests in two dimensions: religious dimension through devotional traditions (ziarah kubur, tahlilan) as spiritual expressions, and civic dimension through reinforcing hubbul wathon minal iman (love of homeland as part of faith) and positioning NU as a strategic government partner. The study concludes that comprehensive Aswaja value reinforcement successfully builds ideological immunity against radicalism while simultaneously strengthening national integration.